1999
DOI: 10.1046/j.1365-2265.1999.00651.x
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular hypertrophy in primary hyperparathyroidism. Effects of successful parathyroidectomy

Abstract: The present data confirm the high prevalence of LV hypertrophy in primary hyperparathyroidism also in a group of patients with an asymptomatic clinical presentation. The correlation between PTH values and left ventricular mass index suggests an action of the hormone in the pathogenesis of LV hypertrophy confirmed also by the decrease of left ventricular mass index after the reduction of PTH levels. The reversal of left ventricular mass index after parathyroidectomy could affect mortality in primary hyperparath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
1
18

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(183 citation statements)
references
References 32 publications
8
153
1
18
Order By: Relevance
“…This may be related to a regression of left ventricular hypertrophy, as demonstrated in a study using echocardiography to evaluate left ventricular hypertrophy in 43 patients with HPT compared to 43 age-and sex-matched controls. 31 This study found that the left ventricular mass index was statistically significantly higher in those with HPT than in the controls and that this correlated with PTH values. Furthermore, there was statistically significant decrease in left ventricular mass index six months after parathyroidectomy.…”
Section: Treatmentmentioning
confidence: 51%
“…This may be related to a regression of left ventricular hypertrophy, as demonstrated in a study using echocardiography to evaluate left ventricular hypertrophy in 43 patients with HPT compared to 43 age-and sex-matched controls. 31 This study found that the left ventricular mass index was statistically significantly higher in those with HPT than in the controls and that this correlated with PTH values. Furthermore, there was statistically significant decrease in left ventricular mass index six months after parathyroidectomy.…”
Section: Treatmentmentioning
confidence: 51%
“…Stefenelli et al (8) have reported LV hypertropy, and valve and myocardial calcifications in a significant number of patients with mean serum calcium levels of 12 mg/dl. In contrast, patients who had a milder increase in serum Ca (11.1 -11.3 mg/dl) were found to have only LV hypertropy but no significant valvular or myocardial calcification (38,39). On the other hand, Längle et al did not find any direct correlation between the severity and the cardiovascular manifestations of PHPT; however, PTH-related skeletal manifestations and valvular calcifications were predictive factors for left ventricular hypertropy (37).…”
Section: Discussionmentioning
confidence: 82%
“…PTH was shown to act as a pro-hypertrophic factor by increasing protein synthesis in vitro (Schluter and Piper, 1998) and as a vasodilator by increasing the intracellular cAMP level, leading to a decrease in calcium influx (Clemens et al, 2001). The mass of the left ventricle was correlated with the PTH level in patients with end-stage renal disease and secondary hyperparathyroidism (Harnett et al, 1988) and in patients with primary hyperparathyroidism (Piovesan et al, 1999). However, no significant correlation between the left ventricular mass and PTH level was found in the general population (Saleh et al, 2003).…”
Section: Introductionmentioning
confidence: 94%